Efeitos do chumbo sobre o desenvolvimento do tecido ósseo de ratas - Mattos, Valéria Gonçalves Albieri (Universidade Federal de São Carlos, 2010)
The aim of this study was to investigate the effects of lead on femurs and vertebrae during development and skeletal maturity of female rats. For this purpose, one month old female rats were treated with lead acetate 100mg/kg BW or saline 0,9% 0,1ml/100g BW . The treatment was administrated by gastric gavage, once a week, during two months. After the treatment period, the animals received only tap water and commercial chow ad libitum until they completed 6, 9 and 12 months of life. The 3 months old groups were sacrificed soon after the treatment. The incorporation of lead in bone tissue occurred in all groups of intoxicated animals. The lead did not interfere the body development of experimental animals. The lead intoxication induced reduced maximum load, stiffness and resilience of the femur in the threepoint bending test in the groups 6, 9 and 12 months of life. The compression test of vertebrae of contaminated rats showed reduction of biomechanical parameters only in skeletally mature rats (9 months). The present study revealed that lead exposure during early stage of development affected the bone mineral profile leading to biomechanical weakness with skeletal maturity. The results allow us to conclude that lead exposure affects the biomechanical properties of mature bone increasing susceptibility to fractures.
Keywords: Medicina experimental - rata; Tecido ósseo; Chumbo; Biomecânica óssea; Rato; Propriedades biomecânicas; Bone tissue; Biomechanical properties; Lead; Rat; CIENCIAS BIOLOGICAS::FISIOLOGIA